2013
DOI: 10.1590/s0103-90162013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitrogen from sugarcane harvest residues and urea for crop nutrition

Abstract: Sugarcane (Saccharum spp.) harvested without burning provides a substantial amount of remains (trash) on soil profiles which can be decomposed and release nutrients contributing to reduce fertilizer needs. The contribution of nitrogen (N) from sugarcane plant residues and fertilizer in sugarcane nutrition was assessed. Plant cane treatments were micro plots of 15 Nlabeled urea, sugarcane trash and root system; the last two to simulate the previous crop residues incorporated into the soil after crop renewal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 25 publications
3
32
0
6
Order By: Relevance
“…Fortes et al (2013) found recovery of trash-N accumulated over a three year period, of 16.9 % and 30.7 % in plots without N fertilizer and plots with 150 kg ha -1 N over the trash, respectively. Based on this result, we adopted a factor of 1.82 (30.7/16.9) to consider the effect of N fertilization in increasing the recovery of trash-N.…”
Section: Recovery Of Trash-nmentioning
confidence: 91%
See 4 more Smart Citations
“…Fortes et al (2013) found recovery of trash-N accumulated over a three year period, of 16.9 % and 30.7 % in plots without N fertilizer and plots with 150 kg ha -1 N over the trash, respectively. Based on this result, we adopted a factor of 1.82 (30.7/16.9) to consider the effect of N fertilization in increasing the recovery of trash-N.…”
Section: Recovery Of Trash-nmentioning
confidence: 91%
“…Recovery of N from previous crop residues (RN-PCR): Fortes et al (2013) studied the recovery of N from aboveground and belowground sugarcane residues by the subsequent sugarcane crop up to four years after residues were applied. Using the data of Fortes et al (2013) and considering aboveground components account for 70 % of the total sugarcane residues and belowground Franco et al (2007).…”
Section: Recovery Of Trash-nmentioning
confidence: 99%
See 3 more Smart Citations